Aplikasi Pupuk Hayati Fosfat dan Bahan Pembenah Tanah Organik untuk Meningkatkan Pertumbuhan dan Hasil Panen Jagung (Zea mays L) pada Tanah Masam - Fiqriah Hanum Khumairah; Anggi Jingga; Betty Natalie Fitriatin; Tualar Simarmata (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
Acidity is still a serious obstacle for maize cultivation due to the very low availability of phosphorus. The use of phosphate biofertilizers, containing phosphate solubilizing bacteria as an active ingredient, together with organic ameliorants was expected to be able to provide phosphorus for plants and increase the organic C content in the soil. Experiment aimed to find the proper application of phosphate biofertilizers along with organic ameliorants to support the productivity of maize on acid soils. A factorial randomized block design was used with phosphate biofertilizers and organic ameliorants as the first factor and doses of inorganic P fertilizer as the second factor, all treatments was equipped with three replications. Results showed that the application of phosphate biofertilizers consisted of Enterobacter ludwigii, Bulkholderia vietnamiensis, and Citrobacter amalonaticus with the composition of chicken manure compost (25%): municipal waste compost (25%): coconut shell biochar (50%) at a dose of 5 tons/ha was able to increase plant dry weight and dry weight of shells per hectare by 248.87 g and 12.960 kg. The application of phosphate biofertilizers and organic ameliorants showed no significant effect to soil C-organic content. Phosphate biofertilizers and organic ameliorants can support the productivity of maize plants on acid soils